APPLICATION OF THE NON-SURGICAL BOVINE EMBRYO TRANSFER TECHNIQUE IN A DAIRY FARMIN THE LIMA MILKSHED - Medrano R., Jonathan (2014)
The study aimed to evaluate the superovulatory response and conception rate byapplying the technique of non-surgical embryo transfer in dairy cows of a commercialfarm in the Lima milkshed. Eight donor cows were used and distributed in two workingyears. Donors were synchronized with estrogens, progestagens and luteolitic agents,superovulated with 400 mg of FSH, and inseminated with two doses of frozen semen. Therecipient animals (n=28) were also distributed in two years. The Pre-synch protocol wasused for estrus synchronization in the first year and the CIDR-synch protocol in thesecond year. The expected day of heat presentation coincided for both donors andrecipients. The recovery of embryos was done seven days post service where embryoswere classified and immediately transferred. Pregnancy diagnosis by transrectalultrasonography was done at day 28 post transfer. A total of 23 embryos were obtained.The embryo recovery rate was 36.5% with high variation between years. Seventeenembryos were transferred and the conception rate was 40% with high variation betweenyears (22.2 and 66.7%). The varied individual response of the donors affected the embryorecovery rate and the synchronization protocol affected conception rate.